The extent of ‘Urf's authority in establishing the legality of matrimonial property - Moawad, Abdel Tawwab Moustafa Khaled (Linguistics and Culture Review, 2021)
This research discusses the proofs cited by proponents of the legality of matrimonial property –during marriage or when marriage is ended by divorce or death- based on the prevailing custom in the Malaysian society. The paper reaches a number of findings, the most important of which is that the Malay custom in question is not in harmony with the requirements of the u?ul? ‘urf; therefore it is considered invalid ‘urf and it cannot be used to establish the legality of matrimonial property from the Shari‘ah perspective. The researcher recommends that for the matrimonial property to be legal, it should take the form of gift, partnership or loan and the specific rulings of these transactions are to be applied.